Botulinum Toxin Therapy for Parkinson's Disease - Wagle Shukla, Aparna; Malaty, Irene A. (Seminars in Neurology, 2017)
Botulinum toxin (BoNT) therapy is frequently employed in the treatment of Parkinson's disease (PD) symptoms. It can effectively ameliorate the symptoms of cervical dystonia, blepharospasm, sialorrhea, and hyperactive bladder. It is increasingly being used for additional PD-related indications including limb dystonia, oromandibular dystonia, tremors, constipation, dysphagia, gastroparesis, and sweating dysfunction. Botulinum toxin treatment has mostly local side effects and does not interfere with dopaminergic therapies prescribed for PD. With the exception of dystonia and sialorrhea, most evidence for BoNT efficacy is derived from studies conducted in nonparkinsonian populations. Thus, the data to inform typical response pattern and side-effect profile in PD are still evolving. Nevertheless, BoNT is widely used and is an important tool in the PD-treatment arsenal. In this review, the authors discuss the current literature on the use of BoNT in various PD-related motor and nonmotor disorders.
Keywords: botulinum toxin; Parkinson's disease; dystonia; blepharospasm; sialorrhea